Aplikasi Sistem Pendukung Keputusan Untuk Menentukan Harga Layanan Teknologi Informasi - Widodo, Edi; Mustafid, Mustafid; Widiyanto, Ibnu (JSINBIS (Jurnal Sistem Informasi Bisnis), 2014)
The effects of recency of information technology (IT) will be invested impaired, this makes it difficult to assess the information technology investment. This study intend to calculate the production cost of IT services with the activity based costing system method, to assess IT investments. This study make the position of IT department as an independent business that sells services to other departments within the organization (IT as a service - ITaaS). To assess the IT investment carried out in 3 stages, 1) Do departmentalize overhead, 2) Calculate the production cost of IT services,3) Perform investment analysis using cash flow simulation with the net present value method. The result of this study is decision support system information to assist management in determining the implementation of IT investments, to do their own (in-house) or purchased from an outside party (outsourced). In this way, losses due to errors in executing IT investments can be avoided, because the analysis is done prior IT investments held. Â  Keywords: IT Investment; Net Present Value (NPV); Activity-Based Costing system (ABC);Value chain; IT as a Service (ITaaS)